2005
DOI: 10.1128/mcb.25.14.5933-5946.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nrf1 and Nrf2 Regulate Rat Glutamate-Cysteine Ligase Catalytic Subunit Transcription Indirectly via NF-κB and AP-1

Abstract: Glutamate-cysteine ligase catalytic subunit (GCLC) is regulated transcriptionally by Nrf1 and Nrf2. tertButylhydroquinone (TBH) induces human GCLC via Nrf2-mediated trans activation of the antioxidantresponsive element (ARE). Interestingly, TBH also induces rat GCLC, but the rat GCLC promoter lacks ARE. This study examined the role of Nrf1 and Nrf2 in the transcriptional regulation of rat GCLC. The baseline and TBH-mediated increase in GCLC mRNA levels and rat GCLC promoter activity were lower in Nrf1 and Nrf2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
185
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 231 publications
(202 citation statements)
references
References 41 publications
15
185
0
2
Order By: Relevance
“…Thyroid hormone and cysteine deprivation induce GCLm expression (Dasgupta et al, 2007). Nrf1, Nrf2, AP-1, NFκB and c-Myc seem to be involved in the regulation of the promoter activity of the GCLm gene (Wild et al, 1999;Yang et al, 2005;Benassi et al, 2006). Interestingly, it has been shown that insulin was unable to change the levels of GCLm mRNA (Okouchi et al, 2006), while GCLc levels were affected by this stimulus in the same report.…”
Section: +mentioning
confidence: 69%
See 2 more Smart Citations
“…Thyroid hormone and cysteine deprivation induce GCLm expression (Dasgupta et al, 2007). Nrf1, Nrf2, AP-1, NFκB and c-Myc seem to be involved in the regulation of the promoter activity of the GCLm gene (Wild et al, 1999;Yang et al, 2005;Benassi et al, 2006). Interestingly, it has been shown that insulin was unable to change the levels of GCLm mRNA (Okouchi et al, 2006), while GCLc levels were affected by this stimulus in the same report.…”
Section: +mentioning
confidence: 69%
“…These and other considerations point to a major regulatory function for GCLm in glutathione synthesis. Some of the above-mentioned stimuli could induce both, GCLc and GCLm (Wild et al, 1999;Yang et al, 2005). However, there is some evidence supporting the specific up-regulation of GCLm.…”
Section: +mentioning
confidence: 90%
See 1 more Smart Citation
“…Third, mutations in multiple regulatory sequences, including the ARE, CRE/AP-1, and E box, were required to abolish HO-1 promoter responsiveness. It is possible that Nrf2 activates the human HO-1 promoter indirectly through AP-1 family members as shown recently for the rat glutamate-cysteine ligase catalytic subunit gene (55). A comparison of the HS-2 region with the previously described E1 enhancer region located at Ϫ4.0 kb of the mouse Ho-1 gene (7,56) reveals that the three StRE sequences of the mouse E1 region (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interplay between Nrf2 and NF-jB signaling is well documented. 45,48 Additionally, small molecule Nrf2 activators have been shown to be effective in inhibiting activation of NF-jB. Xu et al 49 demonstrated that sulforaphane exposure to a human prostate cancer cell line resulted in decreased UVCinduced NF-jB activation.…”
Section: Discussionmentioning
confidence: 99%